Is the genetic integrity of natural populations ex situ preserved with the current sampling, conservation and regeneration approaches? - Camadro, Elsa Lucila (2014)
Acceleration of environment degradation and climate change poses serious threats to both natural and agricultural ecosystems. In fact, the number of endangered plant species at the global level has increased yearly in the last decades, due to anthropic interventions that sum up to the climate change. Samples of natural plant populations, particularly of wild crop relatives, are ex situ conserved in germplasm banks, which have become active in the provision of genetic resources to breeders. The aim of this article is to generate discussion on the adequacy of (a) current protocols for sampling and ex situ conservation of the natural genetic diversity and (b) the actual species paradigm in plants, due to their consequences for this and future generations.